Differential effects of visually induced analgesia and attention depending on the pain stimulation site. (15th November 2020) - Cordier, Larissa; Ullrich, Eva M.; Herpertz, Stephan; Zieglgänsberger, Walter; Trojan, Jörg; Diers, Martin
Abstract: Background: The term 'visually induced analgesia' describes a reduced pain perception induced by watching the painful body part as opposed to watching a neutral object. In chronic back pain patients, experimental pain, movement‐induced pain and habitual pain can be reduced with visual feedback. Visual feedback can also enhance the effects of both massage treatment and manual therapy. The impact of somatosensory attentional processes remains unclear. Methods: In the current study, participants received painful electrical stimuli to their thumb and back while being presented with either a real‐time video of their thumb or back (factor feedback). In addition, using an oddball paradigm, they had to count the number of deviant stimuli, applied to either their back or thumb (factor attention) and rate the pain intensity. Results: We found a significant main effect for attention with decreased pain ratings during attention. There was no main effect for visual feedback and no significant interaction between visual feedback and attention. Post‐hoc tests revealed that the lowest pain intensity ratings were achieved during visual feedback of the back/ thumb and counting at the back/ thumb. Conclusion: These data suggest that the modulation of perceived acute pain by visually induced analgesia may be influenced by a simultaneous somatosensory attention task. Significance: Somatosensory attention reduced experimental pain intensity in the thumb and back in the presence of both congruent and incongruent visual feedback. We found no significant visual feedback effect on the complex interplay between visual feedback and somatosensory attention.